Inhaled Nitric Oxide Treatment for Aneurysmal SAH Patients With Delayed Cerebral Ischemia - Fung, Christian; Z'Graggen, Werner J.; Jakob, Stephan M.; Gralla, Jan; Haenggi, Matthias; Rothen, Hans-Ulrich; Mordasini, Pasquale; Lensch, Michael; Söll, Nicole; Terpolilli, Nicole; Feiler, Sergej; Oertel, Markus F.; et al. (Frontiers in Neurology, 2022)
Background We demonstrated experimentally that inhaled nitric oxide (iNO) dilates hypoperfused arterioles, increases tissue perfusion, and improves neurological outcome following subarachnoid haemorrhage (SAH) in mice. We performed a prospective pilot study to evaluate iNO in patients with delayed cerebral ischemia after SAH. Methods SAH patients with delayed cerebral ischemia and hypoperfusion despite conservative treatment were included. iNO was administered at a maximum dose of 40 ppm. The response to iNO was considered positive if: cerebral artery diameter increased by 10% in digital subtraction angiography (DSA), or tissue oxygen partial pressure (PtiO2) increased by > 5 mmHg, or transcranial doppler (TCD) values decreased more than 30 cm/sec, or mean transit time (MTT) decreased below 6.5 seconds in CT perfusion (CTP). Patient outcome was assessed at 6 months with the modified Rankin Scale (mRS). Results Seven patients were enrolled between February 2013 and September 2016. Median duration of iNO administration was 23 hours. The primary endpoint was reached in all patients (five out of 17 DSA examinations, 19 out of 29 PtiO2 time points, nine out of 26 TCD examinations, three out of five CTP examinations). No adverse events necessitating the cessation of iNO were observed. At 6 months, three patients presented with a mRS score of 0, one patient each with an mRS score of 2 and 3, and two patients had died. Conclusion Administration of iNO in SAH patients is safe. These results call for a larger prospective evaluation. Funding No funding. Clinical trial number https://clinicaltrials.gov/; NCT04988932